Interoperability Implementation Strategy in Command and Control Systems for Security Crisis Management in the Indonesia–Malaysia Border Region - Didik Efendi (CV. Publikasi Indonesia, 2026)
This research aims to analyze the actual conditions of interoperability within the command and control system, identify the obstacles encountered, and formulate strengthening strategies to enhance the effectiveness of security crisis management at the RI–Malaysia border. This research employs a qualitative approach, collecting data through in-depth interviews with seven key informants from the TNI, Polri, Regional Government, and border communities, alongside a review of Pamtas Task Force operational reports. Data analysis follows the Miles, Huberman, and Saldaña model, encompassing data condensation, coding, and data display, reinforced by PESTEL and SWOT frameworks to identify external and internal factors affecting the command and control system. The results show that the command system operates hierarchically from Kodam VI/Mulawarman to the Pamtas Task Force, with coordination conducted through Forkopimda and bilateral cooperation through Patkor Malindo. However, its effectiveness is hampered by the absence of an integrated command center, limited communication technology in blank spot areas, overlapping authorities, and insufficient technical regulations on interoperability. Strengthening strategies derived from the Strengths–Opportunities (SO) approach include: the establishment of an AI-based Integrated Border Command Center (IBCC) 4.0, the adoption of modern technology for real-time data integration, the reinforcement of bilateral defense diplomacy, the empowerment of communities through community-based security, and the enhancement of human resource capacity. The research concludes that optimizing interoperability requires military structural integration, modern technology, inter-agency synergy, and solid bilateral cooperation through an adaptive, collaborative, and sustainable approach.